Breast Carcinoma After Ocrelizumab Therapy in Multiple Sclerosis Patients: A Case Series and Literature Review. (1st September 2021) - Kelsey, Andrew; Casinelli, Gabriella; Tandon, Medha; Sriwastava, Shitiz
Ocrelizumab is a humanized CD20 monoclonal antibody which was approved for management of Relapsing Remitting Multiple Sclerosis (RRMS) and Primary Progressive Multiple Sclerosis (PPMS) in 2017. We present 2 patients, a 67-year-old woman with history of PPMS and a 42-year-old woman with RRMS, who were started on ocrelizumab and were diagnosed with invasive ductal cell breast carcinoma after 2 years of ocrelizumab infusion followed by discontinuation of the drug. Large trials conducted for ocrelizumab showed malignancies in a total of 4 cases with RRMS in OPERA 1 trial conducted over 2 years from 2011 to 2013 (breast cancer, renal cell carcinoma, and melanomas) and in 11 cases with PPMS seen in ORATORIO trial conducted in 2017. There are currently no other published case reports of breast cancer in setting of ocrelizumab use for MS outside of large trials on literature review.